A new Jacquemontia Choisy (Convolvulaceae) species from the Brazilian Amazon forest - Deibson Pereira BELO; Maria Teresa BURIL; Emília ARRUDA; Rafael Batista LOUZADA (Acta Amazonica, 2023)
ABSTRACT A new species of Jacquemontia found in Carajás National Forest, Brazil, Jacquemontia ferricola sp. nov., is described for an area with a unique flora threatened by mining. We provide a diagnosis of the new species, morphological and anatomical descriptions, illustrations, scanning electron microscopy images, with comments on its distribution and conservation status. The new species was compared with the Brazilian Amazonian Jacquemontia species and an identification key is provided.